1980
DOI: 10.1152/jappl.1980.49.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of lungs and chest wall during spontaneous breathing

Abstract: Using a forced oscillation technique, we measured the resistance (Rrs) and reactance (Xrs) of the respiratory system between 2 and 32 Hz at three different lung volumes in 15 healthy subjects and 7 patients with chronic obstructive pulmonary disease. Rrs and Xrs were partitioned, by means of a pressure recording in the esophagus, into the resistance and reactance of lung and airways (L) and the chest wall. The measurements were validated by checking the adequacy of the frequency response of the esophagus, by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 0 publications
9
108
2
Order By: Relevance
“…At random, resistance was measured by the SensorMedics 6200 body plethysmograph (SensorMedics, Yorbe Linda, CA, USA; airway resistance (Raw)), the Jaeger impulse oscillation system (IOS, Erich Jaeger) [1,2] and the Landsèr forced oscillation technique [5,7,10] within a time period of 30-60 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At random, resistance was measured by the SensorMedics 6200 body plethysmograph (SensorMedics, Yorbe Linda, CA, USA; airway resistance (Raw)), the Jaeger impulse oscillation system (IOS, Erich Jaeger) [1,2] and the Landsèr forced oscillation technique [5,7,10] within a time period of 30-60 min.…”
Section: Methodsmentioning
confidence: 99%
“…With the FOT, a pseudorandom noise signal was applied [5,7] linear regressions and dispersions from the line of identity, according to the method of BLAND and ALTMAN [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using linear regression of the Rrs curve, carried out in the 4-16 Hz frequency range, we obtained the resistance at the intercept (R 0 ). (2,10,17) Based on the Xrs curve, the dynamic compliance (Cdyn) of the respiratory system at the 4-Hz frequency was calculated as follows (17,19) : Cdyn = −2ω × f × Xrs, 4 Hz The analysis of R 0 and Cdyn was performed using the values for the variation between prebronchodilator and postbronchodilator measurements in the different groups (control, mild, moderate and severe) and subgroups (BR+ and BR−).…”
Section: Resultsmentioning
confidence: 99%
“…The difference observed between our group 1 and 2 patients is not due to a particular observation tilting the mean in small groups. In particular, there is no The negative slope of resistance at low frequencies associated with a low reactance is not specific to pulmonary vascular congestion and has been described in obstructive lung diseases 14,24,29,30 Mechanical inhomogeneities of the lung and upper airways have usually been invoked to interpret this characteristic Zrs frequency dependence.11 14,30 According to the model described by Mead,3 an increase in slope of resistance vs frequency could be associated with an increase of resistance of the small airways. Numerous animal4'1 and human studies'8 have shown that pulmonary vascular congestion could induce small airways dysfunction, as shown by an increase in closing volume and peripheral airways resistance and by a decrease in dynamic compliance.…”
Section: Discussionmentioning
confidence: 99%